Pengelolaan Manajemen Risiko pada Industri Perbankan - Lis Sintha (JURNAL MITRA MANAJEMEN, 2016)
AbstractThe banking industry is an industry that is laden with risks, especially as it involves themanagement of public money and screened in the form of investment. To minimize therisks faced, bank management should have sufficient expertise and competence, so that avariety of risks that could potentially arise can be anticipated from the beginning, and lookfor a better way of handling it. The types of risks presented by the economists are verydiverse but substantially similar to one another. Broadly speaking, the grouping of riskconducted by economists are almost the same description and its coverage. The biggerand modern bank, the more numerous and complex risks that it faces.Financial risks faced by the banking industry, can be broadly grouped into five (5) majorrisk, namely: (1) credit risk, (2) market risk, (3) liquidity risk, (4) operational risks, and (5 )risk capital. These risks are presented in the financial ratios, indicating that theperformance achieved by management in managing a bank.Bank Indonesia based on the Basel II classifies eight (8) types of risk are generallydivided into two (2) categories of risk, which can be measured (quantitative), namely creditrisk, market risk, liquidity risk, operational risk and risks are difficult to measure(qualitative) that legal risk, strategic risk, reputation risk and compliance risk.Keywords: Risk Management; Basel II; Banking